Lembaga Tabung Haji Kelantan / Nuralia Anis Nasrin Roslan - Roslan, Nuralia Anis Nasrin (Universiti Teknologi MARA, Perlis, 2023)
HRM 666 is a internship course that compulsory for all the Human Resource Management students. Students will be undergo six (6) months of industrial training in their chosen company. As for me, I will undergo my industrial training at Lembaga Tabung Haji Kelantan for six months. This industrial training is because we as a student need to adapt ourselves with the work environment in order to be able to carry out the work well in the future. Furthermore, this report including company's profile andtraining's reflection for getting know more about Lembaga Tabung Haji. There is also SWOT Analysis that I had observed during my six months internship in this company.